Screening for neglected tropical diseases and other infections in refugee and asylum-seeker populations in the United Kingdom. (August 2022) - Cinardo, Paola; Farrant, Olivia; Gunn, Kimberlee; Ward, Allison; Eisen, Sarah; Longley, Nicky
Asylum-seekers and refugees have an increased burden of infections compared with the general population. This has been widely recognised by countries welcoming those fleeing conflict and persecution; however, there are no screening standardised guidelines and regulatory processes. Identification of certain neglected tropical diseases (NTDs) and other infections is important for the health and well-being of the individual in addition to public health and biosecurity. In the United Kingdom, screening for infections at port of entry or after arrival is not mandatory. Those on refugee resettlement programmes will have infection screening as part of their pre-entry health assessment, but no such system exists for those claiming asylum in the United Kingdom. In this article, we have reviewed published, peer-reviewed articles looking at the approaches to screening for NTDs and infectious diseases in the United Kingdom. In addition to this, we have reviewed the literature looking at the acceptability, barriers and facilitators of these screening practices. We found that there is a heterogeneous approach to screening practices in the United Kingdom and a paucity of data to support a single 'best practice' approach. Based on our findings, we have made recommendations and consideration for NTD screening strategies and highlighted important areas for future research.